Maternal vitamin D status in relation to cardiometabolic risk factors in children from the Norwegian Environmental Biobank - Anna Amberntsson; Linnea Bärebring; Anna Winkvist; Lauren Lissner; Anne Lise Brantsæter; Iris Erlund; Eleni Papadopoulou; Hanna Augustin (PLoS ONE, 2025)
Background Maternal 25-hydroxyvitamin D (25OHD) status has been associated with birth weight and childhood growth. Further, maternal 25OHD status may also influence cardiometabolic outcomes in childhood. This study investigated the association between maternal 25OHD concentration in pregnancy and markers of cardiometabolic risk in 7–12-year-old children. Methods Data were obtained from the Norwegian Environmental Biobank (NEB) including 244 mother-child pairs in the Norwegian Mother, Father and Child Cohort Study (MoBa) participating in NEB part I and II. Childhood outcomes investigated were z-scores of anthropometrics, blood lipids and hormones. Associations between maternal 25OHD and individual cardiometabolic risk factors in children were assessed by linear regression, adjusted for maternal pre-pregnancy BMI, maternal education, child’s sex, age and BMI, and tested for interaction with pre-pregnancy BMI. Results Per 10 nmol/L increase in maternal 25OHD, childhood adiponectin z-score increased by 0.067 standard deviations (p = 0.039). There were no associations between maternal 25OHD concentration and any other cardiometabolic risk factor in childhood. Conclusion The results indicate that higher maternal vitamin D status during pregnancy may be related to higher childhood adiponectin z-score, but not with any other cardiometabolic risk marker. Whether adiponectin could be one pathway linking vitamin D to cardiometabolic health remains to be determined.